JOHN RAWLS' JUSTICE REVIEW OF THE RETIREMENT AGE LIMIT FOR INDONESIAN WORKERS - Indra Pambudi Raharjo; Syofyan Hadi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The regulation of the retirement age for workers constitutes a strategic component of labor policy and social protection systems, as it directly affects workers’ economic security, the distribution of welfare, and social justice within industrial relations. In Indonesia, retirement age regulations remain fragmented and have not yet been consolidated into a unified legal framework, potentially resulting in unequal treatment among workers and uncertainty in social protection during the transition to retirement. This study aims to examine the regulation of workers’ retirement age in Indonesia from the perspective of John Rawls’ theory of justice, while also formulating normative implications for the development of socially equitable labor policies, particularly in ensuring equal opportunity and protection for workers from the most vulnerable groups. The study employs a normative legal approach, combining conceptual analysis with a review of statutory regulations. The conceptual approach is applied to investigate Rawls’ theory of justice, particularly the principles of justice as fairness, fair equality of opportunity, and the difference principle, while the statutory analysis examines retirement age regulation within the framework of labor law and the national social security system. The findings indicate that the current regulation of workers’ retirement age in Indonesia does not fully align with Rawlsian principles of justice. Regulatory fragmentation creates disparities in opportunities and social protection among workers, which cannot be morally justified within the framework of justice as fairness. The novelty of this study lies in its normative approach, which positions retirement age regulation as an integral element of the basic structure of society, while emphasizing the urgency of reconstructing retirement age policies based on the principles of fair equality of opportunity and the difference principle, so that the distribution of benefits for the least advantaged groups of workers becomes more equitable.